Otimização de torres de aço para geradores eólicos - Feijó, Bruno Pinho (2010)
Different forms of energy generation have been developed with the intention of offering environmentally friendly alternatives. In the Northeast region of Brazil and especially in the state of Ceará, wind energy has been increasing due to the large potential of wind in the region. To increase the power, increasingly high towers have been used to capture stronger winds. It is noteworthy that the cost of towers, generally made of steel, represents significant portion (20-30%) of the total wind power generation system costs. This work presents two approaches for optimizing the design of tubular towers for wind steel generators. The first considers a prismatic cylindrical steel tower, which is modeled by means of the classical Euler-Bernoulli’s beam theory. The second formulation considers a tower composed of segments of the trunks of cone. The analysis was run by finite element analysis. The design variables that define the structures are the diameters of representative segments and their thicknesses. In the prismatic cylindrical tower, this diameter is unique. The minimum cost is searched by minimizing the weight of the tower. Constraints related to the structural behavior (stiffness, strength and stability in accordance with recommendations of standards) and the manufacturing process and transportation are considered. The manufacturing process gives the diameters of each segment representing a continuous nature, and as a result of commercial availability, the thicknesses of the plates have a discrete nature. The constraints to ensure the safety of the structure followed the standards recommendations. They presented discontinuities in their functions and their derivatives. The discrete nature and the discontinuities hinder the solution of the problem by classical methods of mathematical programming. So, they had been adequately addressed by algorithms based on simulation of the process of Darwinian evolution and principles of genetics, called Genetic Algorithms (GA). Thus, some applications of the formulation are made and solutions are obtained using GA’s. The results are compared with solutions from literature, and the optimum solutions obtained are verified by shell finite elements models using the software ABAQUS.